The Impact of Alcoholic Beverages on Human Health - Anderson, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Alcohol is often perceived as an under-rated risk factor for human health. This book corrects these misperceptions and misinformation by providing up to date reviews and publications that consider the impact of alcoholic beverages on human health in the domains of toxicity, carcinogenicity, genotoxicity, foetal toxicity, neurotoxicity, impacts of alcohol on the gastro-intestinal system (including nutrient deficiencies), cardiovascular system, injuries, body weight and communicable diseases. The reprint considers how the impact of alcohol on human health can be mitigated - through, for example, improved labelling on nutrients and health warnings, better policy measures, and actions by alcohol producers on their products through reformulation to lower alcoholic strength.